Effect of type of reducing sugar on maillard reaction of gelatine from different sources - Ahmad Fadzillah, Nurrulhidayah; Hamid, Anis Hamizah; Othman, Rashidi; Rohman, Abdul; Abdullah Sani, Muhammad Shirwan; Muhammad, Nurul Widad Fitri (2018)
Increasing awareness among Muslims with respect to the Halal status of food has intensified efficient and effective food-source authentications that are science-based-protocol. Traceability of gelatine to its source remains a daunting scientific task prior to classification of gelatine Halal status. The methodology of this study involves UV-Vis spectroscopic measurement of the degree of browning during Maillard reaction of different gelatine sources with a different type of reducing sugar. Xylose has the highest browning value (A420nm) among all types of reducing sugar. Principle Component Analysis (PCA) was used to differentiate the sources of gelatine. The output from this study will go a long way to reduce cost and time for authentication of gelatine sources and ensure achievement of Halal assurance among consumers at large.